ANALYSIS OF MAINTENANCE COSTS AND PUBLIC SATISFACTION LEVELS TOWARD SOOKO GREEN OPEN SPACE DEVELOPMENT - Putera, Rendra Pramana; Oetomo, Wateno; Sajiyo, Sajiyo (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Electronic media information obtained by the author states that the Mojokerto Regent ordered the Mojokerto District Environment Office to create a Green Open Space that is planned to be built in each sub-district. In 2022, the Mojokerto District Environment Office planned the Sooko Green Open Space by making a DED and continued to carry out its construction and ended at the end of 2023. The research method used is using the method: Net Present Value (NPV) to determine the value of profit or loss, Benefit Cost Ratio (BCR) to determine the comparison of the value of profit and loss, Payback Period (PbP) to determine how long it takes to return the capital that has been spent, and Likert scale calculations to determine how much the level of community satisfaction on the existence of Sooko Green Open Space. The results showed that the Sooko green space development investment is feasible. This can be seen from the NPV> 0 value of Rp 3,213,731,030, the IRR value exceeds the expected interest rate of 22.7%, the Payback Period of returning the investment value of slum housing improvement development occurs in the 4th year 6 months, precisely in 2028. The amount of maintenance costs for the development of Sooko with all facilities and infrastructure is Rp315,291,605, - every year. Based on Excel calculations of the level of community satisfaction from questionnaires that have been obtained, the average value is 90% so that it meets the criteria of Very Satisfied with a standard deviation of 49%.